Self-directed learning in massive open online courses and its application at the workplace: Does employer support matter? - Hamori, Monika (Elsevier, 2023)
This paper explores how employer support for self-directed learning in courses that are created and controlled by third parties (specifically, massive open online courses—MOOCs) influences employed learners’ course performance, internal application of skills (their motivation to use the course content in their current job and organization, and their postcourse training transfer), and external application of skills (their motivation to use the courses to find a new job, and postcourse job search). While inducements (tuition reimbursement and time off from working hours) are negatively related to learners’ external application of skills, they do not increase training transfer at the current employer after the MOOC, possibly because they fail to strengthen learner effort during the course. Expectation-enhancing support for the MOOCs (including the courses in performance evaluations, and requesting that learners take courses) does increase the internal application of skills, but also their external application.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 4 - Educación de calidad; ODS 8 - Trabajo decente y crecimiento económico; Training; Online learning; MOOCs; Training transfer; Job search